Peningkatan Kasus Bunuh Diri Di Batam: Analisis Faktor Penyebab Dan Strategi Pencegahan - Jowan, Jowan (Prosiding, 2024)
Suicide rates in Batam have risen in recent years. The goal of this research is to identify the major causes of this disease and develop effective prevention strategies. According to statistical data analysis, in-depth interviews, and community surveys, the leading causes of suicide include social pressure, mental health conditions, and financial difficulties. This study suggests several prevention techniques, including expanding access to mental health care, raising public awareness, intervening in legislation, and providing specialized training for health workers. This technique is intended to reduce the suicide rate in Batam while also improving the community's mental health.